HUBUNGAN IBU HAMIL DENGAN PREEKLAMSIA BERAT (PEB) TERHADAP ANGKA KEJADIAN BERAT BADAN LAHIR RENDAH (BBLR) - Sri Martini; Rosmala Kurnia Dewi (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
Hypertension in pregnancy is a medical problem that often occurs during pregnancy and can cause complications in pregnancy. Preeclampsia in pregnancy causes various effects. According to the Preeclampsia Foundation in the American Pregnancy Association (2018), it is said that preeclampsia will cause insufficient blood to reach the placenta, which causes the intake of nutrients and oxygen to the fetus to be reduced and affects the fetal weight. The purpose of this study was to determine the relationship between pregnant women and severe preeclampsia (SP) on the incidence of low birth weight (LBW). This research uses analytical research methods with retrospective approach. Bivariate analysis is used to determine the relationship to the object of research using thetest Spearman Correlation. This research was conducted at Permata Bunda Hospital (RSPB) Purwodadi using secondary data from medical records as research data. Research subjects were pregnant women who gave birth with a sample of 33 respondents using a total sampling system. From the results of the study, 14 (82.4%) pregnant women with SP who gave birth to babies with LBW and 3 (17.6%) pregnant women with SP. Meanwhile, 2 pregnant women without SP who gave birth to LBW were 2 (12.5%) and 14 (87.5%) non-pregnant women who gave birth without SP. Spearman test results with a significant value of 0.000 (p <0.05) with a correlation coefficient of 0.699 which indicates a strong correlation and a positive value. This shows that there is a significant relationship between pregnant women and SP on the incidence of LBW.